PENGARUH PERMAINAN DIXI TERHADAP KEMAMPUAN BERBICARA PADA ANAK USIA 5-6 TAHUN DI KB AL HUSNAYAINI KECAMATAN TAMPAN KOTA PEKANBARU - Mastina Nova; Ria Novianti; Febrialismanto Febrialismanto (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This research was based on the researcher’s observation at KB Al Husnayaini, Tampan Sub-district, Pekanbaru City. The observation proved that the speaking ability of protégé still did not develop optimally. Hence, Dixi game was needed to increase protégé’s speaking ability. This research aimed to review the effect of Dixi game towards speaking ability of 5-6 years old children. This research was conducted at KB Al Husnayaini, Tampan Sub-district, Pekanbaru City, from July until April 2019. This research used experiment method with one group pre-test post-test design with 16 number of sample. This research used observation sheet to collect the data. The data analysis technique used t-test by using I.BM SPSS Statistics Program version 20. According to the data analysis, it was obtained tcount of 9.051 greater than ttable of 2.131 with sig 0.000 < 0.Key Words: Dixi Game, Speaking Ability